Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. Digital Leadership and its Relationship to Change Management among Female Principals of Public Primary Schools in Riyadh City Ms. Fadaha Saeed Al-Qahtani, Dr. Hessh Saad Al-Arifi 2. The Level of Dialogue Skills for Tenth and Eleventh-Grade Students in Al-Batinah North Governorate Schools in the Sultanate of Oman from Their Perspective Mr. Mohammed Salim Ali Al-Jahwari, Prof. Jawhar Abdul Qadir Al-Jammoussi 3. The impact of modern trends in education on the use of learning strategies for people with mental disabilities for the secondary stage from the point of view of teachers in the city of Makkah Ms. Hanaa Fahad Al-Sowat 4. Obstacles to the implementation of professional learning communities among UNRWA school teachers in the Jerusalem; Jericho Area from teachers’ perspective Dr. Sahar Said Marbou 5. The Relationship between Positive Thinking and Psychological Health Dimensions in Female Students at the College of Education, Hail University Ms. Malkah Murdhi Almutawaa 6. Successful Intelligence and its Relationship to the Cognitive Holding Power among Umm Al-Qura University Female Students Ms. Asmaa Mohammad Hashem Azouz , Prof. Nawar Mohammad Saad Al-Harbi 7. Refocusing Positively and Its Relationship With (Analytic–Global) Cognitive Style Among University Students Dr. Salwa Faiq Abd 8. Education Between Entertainment and Training: An Applied Study on Public Schools in Mahayel Asir Province Ms. Layla Ahmed Al-Habiri